Primary palliative care research: opportunities and challenges. Issue 4 (12th February 2019) - Barclay, Stephen; Moran, Emily; Boase, Sue; Johnson, Margaret; Lovick, Roberta; Graffy, Jonathan; White, Patrick L; Deboys, Brenda; Harrison, Katy; Swash, Brooke
Abstract : Introduction: Primary care has a central role in palliative and end of life care: 45.6% of deaths in England and Wales occur under the care of primary care teams at home or in care homes. The Community Care Pathways at the End of Life (CAPE) study investigated primary care provided for patients in the final 6 months of life. This paper highlights the opportunities and challenges associated with primary palliative care research in the UK, describing the methodological, ethical, logistical and gatekeeping challenges encountered in the CAPE study and how these were addressed. The study methods: Using a mixed-methods approach, quantitative data were extracted from the general practitioner (GP) and district nurse (DN) records of 400 recently deceased patients in 20 GP practices in the East of England. Focus groups were conducted with some GPs and DNs, and individual interviews held with bereaved carers and other GPs and DNs. The challenges addressed: Considerable difficulties were encountered with ethical permissions, with GP, DN and bereaved carer recruitment and both quantitative and qualitative data collection. These were overcome with flexibility of approach, perseverance of the research team and strong user group support. This enabled completion of the study which generated a unique primary palliative care data set.